Establishing a Tight Link between Students and Society Environment for Education 4.0 – An Online Interaction Case Study - Le, Phuong Truong; Tran , Thi Thuy; Nguyen , Huu Chuc; Do, Thi My Trang; Nguyen, Thi Lai Giang; Jiang, Lai (Journal of Technical Education Science, 2022)
This paper presents research results on online interaction for higher education toward 4.0 education. In addition to online interaction in universities through learning management systems, this study builds a model of online interaction between universities and enterprises and presents methods for implementing different types of online special terms outside the academic environment such as virtual reality tours, virtual internships, and virtual career counseling. The analysis has shown that creating a virtual interactive environment outside the university has brought lots of benefits such as saving cost and time, personalizing learners, changing awareness about digital technology, diversifying learners’ approach.